3-O-(E)-p-Coumaroyl betulinic acid possess anticancer activity and inhibit Notch signaling pathway in breast cancer cells and mammosphere. (1st September 2020) - Kushwaha, Prem Prakash; Singh, Atul Kumar; Shuaib, Mohd; Prajapati, Kumari Sunita; Vardhan, Pothabathula Seshu; Gupta, Sanjay; Kumar, Shashank
Abstract: Activation of Notch signaling is associated with tumor aggressiveness, poor clinical outcome and drug resistance in breast cancer patients. Targeting Notch signaling with small molecule inhibitors may be a better strategy for anticancer drug development. We identified 3-O-(E)-p-Coumaroylbetulinic acid (CB) as a lead compound and potent inhibitor of Notch signaling pathway. Treatment of human breast cancer MBA-MD-231 and T47D cells with CB resulted in a dose- and time-dependent inhibition of cell viability and G0/G1-phase cell cycle arrest. This effect was associated with a marked decrease in the expression of cyclin D1 and its activating partner, cyclin-dependent kinase 2 with concomitant increase in cyclin kinase inhibitor p21, operative in G1-phase of the cell cycle. CB treatment induced early apoptosis in breast cancer cells as evident by increase in cleaved caspase-3, decrease in Bcl2 and survivin, surge in reactive oxygen species and disruption of mitochondrial membrane potential. CB treatment altered Notch target genes viz . Hes1, Hey1 and E-cadherin at mRNA and protein level in time-dependent manner along with decrease in Notch promoter activity at IC50 concentration. Furthermore, CB treatment decreased mammosphere formation in MCF-7 cells through down-modulation of the Notch signaling pathway and suppression of self-renewal markers such as c-Myc, SOX-2 and CD44. Our findings demonstrate that CB possess anticancer activity in breast cancer cells and suppresses self-renewal ability in the mammosphere as a result of modulation in cell-cycle machinery, disruption of mitochondrial function, induction of apoptosis, and Notch inhibition. Graphical abstract: Image 1 Highlights: 3-O-(E)-p-Coumaroyl betulinic acid induces apoptosis in breast cancer cells. 3-O-(E)-p-Coumaroyl betulinic acid arrest cell cycle in breast cancer cells. 3-O-(E)-p-Coumaroyl betulinic acid down-regulate Notch signaling pathway. 3-O-(E)-p-Coumaroyl betulinic acid suppress stemness markers in mammosphere.